2015
DOI: 10.18267/j.pep.515
|View full text |Cite
|
Sign up to set email alerts
|

The Capital Structure Management in Companies of Selected Business Branches of Building in Conditions of the Czech Republic

Abstract: Abstract:Current paper has focused on the capital structure management theories. The theoretical part of the study fi rstly highlights the diff erences between trade-off theories and pecking order theories. In the empirical part there are then proved some signifi cant relationships between fi nancial indicators (debt/equity ratio and return on equity) of homogenous data sample from the Czech branch of building area. The aim of the study is to prove the diff erences between the capital structure development tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…That is, the classic scheme of economic incentives for top managers consists of a fixed part (salary), additional surcharges (stock options) and bonuses and additional benefits (quarterly and annual premiums, car insurance, life insurance, etc.). The authors of [15] found that "the most attractive forms of incentives for managers are salary increases (18.85%), payment of bonuses and bonuses (18.2%), career growth (16.9%)" [29]. Given this and summarizing the existing approaches to the formation of the system of material incentives for top managers according to [4], [5], [25], we can identify two main indicators of this system: the share of salaries (basic and additional) of top managers in the general payroll (GP) (𝒚 𝟏 ) and the share of bonuses and other rewards of top managers in GP (𝒚 𝟐 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…That is, the classic scheme of economic incentives for top managers consists of a fixed part (salary), additional surcharges (stock options) and bonuses and additional benefits (quarterly and annual premiums, car insurance, life insurance, etc.). The authors of [15] found that "the most attractive forms of incentives for managers are salary increases (18.85%), payment of bonuses and bonuses (18.2%), career growth (16.9%)" [29]. Given this and summarizing the existing approaches to the formation of the system of material incentives for top managers according to [4], [5], [25], we can identify two main indicators of this system: the share of salaries (basic and additional) of top managers in the general payroll (GP) (𝒚 𝟏 ) and the share of bonuses and other rewards of top managers in GP (𝒚 𝟐 ).…”
Section: Resultsmentioning
confidence: 99%
“…Some of them are motivated to provide strategic changes, and other are motivated only to support strategic status quo. Work of Růčková and Heryán [29] examines the possible phenomena of separation of top-managers from positions of the owner of company that requires to increase attention to the questions and instruments of stimulation of the first.…”
Section: Introductionmentioning
confidence: 99%
“…He try to exploit the differences between the capital structure decisions for various degrees of free float rate and foreign paid in capital, and for those that have various market values. Petra and Heryán (2015) study the differences between the capital structure developments based on the type of the Czech companies' ownership in the selected NACE industrial branch with financial indicators of 57 building companies with turnover of more than CZK 1.5 billion. This study found that separation of managers from owner's positions.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Symbols and are the constant of the model and residual part in the GMM model. The reason for choosing the above mentioned indicators also comes from the performed studies (such as Nivorozhkin [16], Hernardi & Ormos [9], Crnigoj & Mramor [4], Růčková [20], Růčková & Heryán [21]) that considered particularities of the European environment, mainly weaker availability of the market data. It is just the unavailability of the market data that makes it impossible to apply studies performed in the United Stated of America as most of their models mainly use the market value of the company as a factor.…”
Section: Analysis Of the Functional Relation Of The Building Industrymentioning
confidence: 99%